2011
DOI: 10.1021/ie102255r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polyaniline Nanofibers by High Gravity Chemical Oxidative Polymerization

Abstract: To develop a suitable method for the mass production of polyaniline (PANI) nanofibers, the preparation of PANI nanofibers was carried out by high gravity chemical oxidative polymerization (HGCOP) in a rotating packed bed (RPB) for the first time. The influences of operating conditions, e.g., aniline concentration, high-gravity level, reaction temperature, and dopants, on the morphology of PANI nanofibers were investigated in detail. FTIR, UV−vis, XRD, molecular weight, and conductivity analyses were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 42 publications
1
43
0
Order By: Relevance
“…Although rapid mixing polymerization is considered as the simplest approach with no requirement for organic solvent or other assisting techniques in producing PANI nanofibers, the relatively low aniline concentration in this process would be an obstacle for prepare PANI nanofibers on a large scale. High‐gravity chemical oxidative polymerization in a rotating packed bed (RPB) with a higher aniline concentration was adopted to solve the problem for the mass production of PANI nanofibers by chemical oxidative polymerization. The formation of PANI nanofibers in the chemical oxidation polymerization approach consists of three main steps: chemical reaction, nucleation and growth.…”
Section: Preparation Of Pani Nanofibersmentioning
confidence: 99%
“…Although rapid mixing polymerization is considered as the simplest approach with no requirement for organic solvent or other assisting techniques in producing PANI nanofibers, the relatively low aniline concentration in this process would be an obstacle for prepare PANI nanofibers on a large scale. High‐gravity chemical oxidative polymerization in a rotating packed bed (RPB) with a higher aniline concentration was adopted to solve the problem for the mass production of PANI nanofibers by chemical oxidative polymerization. The formation of PANI nanofibers in the chemical oxidation polymerization approach consists of three main steps: chemical reaction, nucleation and growth.…”
Section: Preparation Of Pani Nanofibersmentioning
confidence: 99%
“…The main characteristic peaks of PANI located at 1564 and 1487 cm À1 are assigned to the C5 5C stretching vibration of quinoid rings and benzene rings. Other peaks located at 1298, 1131, and 799 cm À1 are attributed to C-N stretching mode, N5 5Q5 5N stretching mode (with Q representing the quinoid ring), and C-H bonds of benzene rings, respectively [29,34]. The main characteristic peaks of PG10 are almost the same as those of PANI except for the small peak pointed out by the dash line, illustrating the existence of GN in PG10.…”
Section: Characterizations Of Pani/gn Nanocompositesmentioning
confidence: 86%
“…The solid combination between PANI and GN sheets helps to improve the electrochemical performance of the nanocomposites. Previously, it has been shown that increasing aniline concentration to 0.5 M has no significant effect on the morphology of PANI nanofibers simply because of the assistance of RPB [29]. However, the challenge lies in the dispersion of GN.…”
Section: Effect Of An Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Different factors affect conductivity of PANI with the most important being the doping level, oxidation state, crystallinity, particle morphology, molecular weight, interior intrachain interactions, etc. [61]. By comparing conductivity and doping values, it is apparent that a good correlation exists between these two sets of data.…”
Section: Characterization Of Precipitated Powdermentioning
confidence: 89%